Resillience with Managerial Capabilities of Perdana Medica Mother and Child Hospital of Surabaya in Facing Corona Virus Disease 2019 (Covid-19) and New Normal Adaptations - Khoirul Umam; Katmini (Journal for Quality in Public Health, 2022)
Covid-19 has had a tremendous impact, including on the leadership of managers in hospitals, they are required to act quickly and make total changes in the management field. in these difficult times one's managerial ability and resilience can be assessed. at RSIA Perdana Medica Surabaya, has decided not to accept referrals for Covid-19 patients, and the results of the study show that the lower one's resilience, the lower one's managerial ability. The research instrument used is the researcher himself. Qualitative research has no choice but the researcher himself as the main research. Because everything does not yet have clarity starting from the problem, research focus, research procedures used until the results are still uncertain.